A cone-beam computed tomography study on the morphometry of the mandibular molars and their relative root lengths to the mandibular height - Ngeow, Wei Cheong; Redzuan, Nur Redannia; Mat Nawawi, Nur Nabilah Aisyah (Penerbit Universiti Sains Malaysia, 2020)
The first, second and third mandibular molars (M1, M2, M3) show variations in the number of cusps and some distinction in size, occlusal design, and the relative lengths and number of roots. However, there are also genetic and racial related variations within them. This study determined the tooth length and related root-to-crown ratio (RCR), and root morphology variations in M1 and M2. We also determined the root length relative to the mandibular height of these teeth. Sixty-one cone- beam computed tomography (CBCT) images of patients who had a good set of lower teeth with no sign of mandibular pathology or defect were included. Relevant measurements were made along the axes of the mesial and distal roots of these mandibular molars. The measurements obtained were used to calculate RCR and root-to-mandible (R/M) ratio. The crowns of 226 teeth and 465 roots were reviewed in 61 CBCTs of Malay patients. M1 and M2 were 19.41 mm and 18.15 mm long. The respective anatomical RCR and clinical RCR were 1.90 and 1.59 for M1, and 1.86 and 1.60 for M2. Thirteen molars (5.8%) presented with three roots, with twice the number affecting M1 than M2. More M1 (4.3%) had C-shaped morphology than M2 (1.8%). The R/M ratio at M1 was 42.32% and, at M2 this was 43.94 %. In summary, the morphometric measurements of M1 and M2 in Malay were established. These teeth did not have a high prevalence of supernumerary roots, but there is a high prevalence of C-shaped morphology in M1. http://aos.usm.my/ © Penerbit Universiti Sains Malaysia. 2020